Term and preterm labor: decreased suppressive activity and changes in composition of the regulatory T-cell pool - Schober, Linda; Radnai, Diana; Mahnke, Karsten; Sohn, Christof; Steinborn-Kröhl, Andrea (Immunology & cell biology, 2012)
Regulatory T cells (Tregs) exert a key role in tolerance induction to the semi-allogeneic fetus. Currently, it is not known whether immunological rejection processes are involved in the induction of normal term or irresistible preterm labor. In this study, we examined whether there were differences in the percentage of the total CD4+CD127low+/−CD25+FoxP3+-Treg-cell pool, its suppressive activity and its composition with distinct Treg subsets (HLA-DRlow+-, HLA-DRhigh+-, HLA-DR−- and naive CD45RA+-Tregs) between preterm and term laboring women. We found that its percentage was decreased neither in term nor in preterm laboring women. Its suppressive activity was strongly diminished in preterm laboring women and to a lesser extent in spontaneously term laboring women. During the normal course of pregnancy, its composition changed in such a way that the percentage of naive CD45RA+-Tregs increased while the percentage of the highly suppressive HLA-DRlow+- and HLA-DRhigh+-Tregs decreased significantly until term. With the onset of spontaneous term labor this phenomenon was reversed and reached significant values postpartum. In addition, we confirmed that both the decreased percentage of HLA-DR+-Tregs within the total Treg-cell pool and their decreased level of HLA-DR expression (depending on the percentage of HLA-DRlow+- and HLA-DRhigh+-Tregs) had a reducing effect on the suppressive activity of the total Treg cell pool in preterm laboring women. However, spontaneous term delivery was associated with increasing percentages of HLA-DR+-Tregs and increasing HLA-DR expression of this Treg subset. Therefore, it becomes apparent that the mechanisms inducing term or preterm labor may be completely different.